2001
DOI: 10.1007/s004230100209
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of free gastrointestinal tumor cells in peritoneal lavage detected by immunocytochemistry and polymerase chain reaction

Abstract: ICC is a useful method for detection of tumor cells in peritoneal lavage. In contrast, half-nested RT-PCR cannot be recommended, as the detection rates are unproportionally high, obviously as a result of CEA-mRNA expression in nontumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
1
19
0
1
Order By: Relevance
“…As we know, serosal invasion appears to be mainly responsible for the exfoliation of free cancer cells into the peritoneal cavity [11] . It has been reported that approximately half of patients with serosal invasion develop peritoneal recurrence even if curative resection is performed [6,7,28] . In general, although using the presence of telomerase activity did not show results that surpass PLC methods, the test might offer the possibility of detecting cancer cells in cytologynegative specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we know, serosal invasion appears to be mainly responsible for the exfoliation of free cancer cells into the peritoneal cavity [11] . It has been reported that approximately half of patients with serosal invasion develop peritoneal recurrence even if curative resection is performed [6,7,28] . In general, although using the presence of telomerase activity did not show results that surpass PLC methods, the test might offer the possibility of detecting cancer cells in cytologynegative specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal dissemination is the most frequent pattern of recurrence in patients with gastric carcinoma [5] . About 50%-60% of gastric cancer patients with serosal invasion after curative resection eventually developed peritoneal metastases [6,7] . The incidence of peritoneal recurrence after curative resection was 13.46% and the survival after peritoneal recurrence was 4.9 mo in average [8] .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, cytokeratin 19 mRNA lacks specificity for gastrointestinal cancer. It should be noted that Broll et al do not recommend PCR-based analysis of CEA transcripts for detecting occult tumour cells in peritoneal lavage because they found high false positive rates; five of 13 healthy control peritoneal lavage samples (38%) yielded positive results 11 . However, CEA positivity was detected in 63% of tested peritoneal lavage samples from pancreatic cancer patients (47/75) and PCR-positive patients showed in agreement with our observation poorer overall survival (P=0.04).…”
Section: Discussionmentioning
confidence: 99%
“…Especially in the experimental setting studied by Katsuragi et al (2007), one should consider that CEA expression may be induced in peripheral blood mononuclear cells by cytokines (Jung et al, 1998;Goeminne et al, 1999), as increased concentrations of an array of cytokines characterise peritoneal fluids of cancer patients (Chechlinska et al, 2007). Furthermore, peritoneal lavage samples of cancer-free patients were found to contain CEA transcripts (Broll et al, 2001). In addition, normal granulocytes that are likely to be recruited to peritoneal cavity (Hau, 1990) have been shown to express CK 20 (Jung et al, 1999;Kruger et al, 2001).…”
Section: Sirmentioning
confidence: 99%